Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest - Escárraga, Mayron E; Lattke, John E; Azevedo, Celso O (Zootaxa, 2017)
The male of the endangered ant Dinoponera lucida Emery is described, providing morphometric measurements, high-resolution images, and a distribution map of the species. This ant inhabits the Brazilian Atlantic forest, an ecosystem strongly impacted by fragmentation. The males show clear morphological differences from the known males of other species of Dinoponera. We briefly discuss the relevance of the male description for the conservation strategies of this ant.